Experimental Analysis of the Potential Induced Degradation Effect on Organic Solar Cells - S. C. Akcaoğlu; G. Martinopoulos; C. Zafer (International Journal of Photoenergy)
Renewable energy applications are increasing daily, and solar electricity, in the form of photovoltaics, is getting more and more important worldwide. As photovoltaics are connected both in series and in parallel, the panels are exposed to high potentials compared to the ground; thus, high voltage stress (HVS) occurs. The scope of this paper is to analyze experimentally the potential induced degradation (PID) in organic solar cells. To that end, organic solar cells are manufactured and are then undergone a series of voltage-dependent degradation and time-dependent voltage degradation tests. In addition to that, they are also exposed to gaseous oxygen, oxygen plasma, air degradation, and annealing, and the degradation effects are compared with PID results. From the analysis, it is apparent that annealing, air, gaseous oxygen, and oxygen plasma degradation have similar effects with PID, while due to simple diode characteristics, organic cells proved to be relatively durable to potential induced degradation. At low voltages (10 V), the organic cells withstood degradation adequately, with a drop of 23% in their initial efficiency. As voltage increased, the degradation rate increased considerably reaching a 93% efficiency drop when 30 V was applied for 20 minutes.